The Knowledge, attitude, and practice of oral hygiene among pregnant women attending antenatal clinic in Ekiti State University Teaching Hospital, Ado, Ekiti State, Nigeria - Adeshola Adelekan Ajetunmobi; Anuoluwapo Deborah Ajijola; Adebayo Adeneye Sheyin (Orapuh Journal)
Introduction